Using Standardized Case Vignettes to Evaluate Nursing Home Staff Recognition of Delirium and Delirium Superimposed on Dementia - Fick, Donna M. (Ann Longterm Care, 2013)
The purpose of this study is to describe nursing home staff knowledge regarding delirium detection and the most common causes of delirium. Specific aims that guided this study include identifying the rate of nurse recognition of delirium and delirium superimposed on dementia (DSD), including different motoric subtypes of delirium, using standardized case vignettes, and exploring what nursing home staff describe as the potential causes of delirium. The study showed overall poor recognition of delirium and DSD, which did not improve over time. Interventions have the potential to increase the early detection of delirium and DSD by the staff and warrant development.